Evaluasi Kesesuaian Lahan Tanaman Pangan Pada Lahan Sawah Menggunakan Sistem Informasi Geografis di Kecamatan Sidemen, Kabupaten Karangasem, Bali - Kezia Angelia Febyna Putri; Ni Made Trigunasih; I Made Mega (Nandur, 2023)
This research aims to determine the suitability of actual and potential land for food crops, limiting factors and efforts to improve them as well as appropriate land use directions in Sidemen sub-district, Karangasem. The method used in this research is a survey method and matching the data the quality/characteristics of the land with the requirements for plant growth. The food crops evaluated included rice plants, corn and soybeans. The results of the land suitability evaluation show that the actual land suitability class for food crops (rice, corn, soybeans) are classified as S3 (marginally suitable) to N (not suitable) with limiting factors such as rainfall, P- available, slope, erosion hazard and texture. For land suitability classes, potential food crops (rice, corn, soybeans) are classified as S1 (very suitable) to N (not suitable) with the limiting factors being slope and texture. Efforts to improve that can be done in overcoming the limiting factors include irrigation, applying fertilizers, and making terraces.